Recurrent pleural effusion in patient with liver cirrhosis – a case report (World Journal of Current Medical and Pharmaceutical Research, 2021)
Liver cirrhosis is caused by necrosis of liver cells leading to fibrosis and nodule formation. Structural abnormalities of the liver causing impaired hepatocyte function and portal hypertension. Hepatic hydrothorax is a less common pulmonary complication of portal hypertension. We present a 47 years old man with liver cirrhosis and recurrent massive pleural effusion. Diagnosis can be challenging because it can be associated with pulmonary or systemic disorders. Pleural fluid analysis is necessary to differentiate transudate or exudate as the cause of pleural effusion. Thoracentesis is done to reduce the complaints experienced by the patient.